Antigua and Barbuda. Significant achievements 2010-2017 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Antigua and Barbuda are identified, during the period from 2010 to 2017, with respect to the needs and interests of the country, strengthening issues such as health and food safety, through the Codex Alimentarius, marketing, agro-processors, production value chains, food preservation, financial education, data and dissemination methods. Finally, work was done to improve entrepreneurship, marketing and the inclusion of women producers.